(untitled) (Revista de História da UEG (REVHIST), 2022)
In England from 1455 to 1485, amidst several other conflicts, a dynastic dispute called War of the Roses took place, in which the nobles and other subjects of the kingdom sought different justifications to defend or attack the two prominent royal houses, the Lancaster - headed by Henry VI (1421-1471) – and York – represented by Edward Plantagenet (1442-1483). As the clashes unfolded and with the constant changes in the throne, the requests for royal pardon increased, hoping to count on the pious qualities of the sovereign. With this in mind, using two chronicles, the Chronicle of the Rebellion in Lincolnshire, 1470 and the History of the Arrival of Edward IV in England and the final recovery of his kingdoms from Henry VI (1471), both developed by anonymous authors, we will work the descriptions about the granting of pardon and the way that such narratives sought to exalt the virtues of then King Edward IV (1461-1470; 1471-1483). Since the sovereign should act in the name of the commonweal, supported by the values ​​of Christian morality, we will seek to show how such writings justified the legitimacy of this monarch and his actions in war through his piety and mercy, showing us the importance that such characteristic had for the longevity of the reign of Edward IV and the organization of the English kingdom. Keywords: Royal Pardon. England. 15th century.